Exploring the relationship between proactive personality, individual innovation, and mental health in university students - Mahmut Kilic; Güllü Uslukilic; Nursel Üstündağ Öcal (BMC, 2024)
Abstract Purpose The aim of this study is to determine the effects of proactive personality and individual innovation characteristics of university students on their mental health together with their socio-demographic characteristics. Methods This cross-sectional study was conducted among students of Yozgat Bozok University in 2022. Data was collected using a sociodemographic information form, Individual Innovation Scale (IIS), Proactive Personality Scale (PPS), and the Depression-Anxiety-Stress Scale (DASS-21). The questionnaire forms were presented to students online through Google Forms. Data were analyzed by t-test, ANOVA, correlation and multinomial logistic regression (MLR). Results In this study, the mean scores of the anxiety, depression and stress subscales of DASS were found to be 6.0 ± 3.7, 6.8 ± 4.4 and 7.4 ± 3.8, respectively. The percentage of students showing moderate levels of anxiety, depression, and stress symptoms were 22.2%, 32.0%, and 15.1%, respectively, while those with high or very high levels of symptoms were 31.5%, 17.0%, and 9.8%, respectively. This study provides evidence that proactive personality, individual innovativeness traits, age, and familial characteristics may not significantly influence anxiety, depression, or stress in college students. The probability of students showing moderate and high levels of mental health symptoms was found to be associated with being female and having poor health status. Conclusion Anxiety was found to be the most common mental health problem among university students, followed by depression and stress. No relationship was found between students' proactive personality, individual innovation traits, and their mental health.